Genomic array as compared to karyotyping in myelodysplastic syndromes in a prospective clinical trial. Issue 7 (31st March 2017) - Stevens‐Kroef, Marian J.; Olde Weghuis, Daniel; ElIdrissi‐Zaynoun, Najat; van der Reijden, Bert; Cremers, Eline M. P.; Alhan, Canan; Westers, Theresia M.; Visser‐Wisselaar, Heleen A.; Chitu, Dana A.; Cunha, Sonia M.; Vellenga, Edo; Klein, Saskia K.; et al.
Abstract: Karyotyping is considered as the gold standard in the genetic subclassification of myelodysplastic syndrome (MDS). Oligo/SNP‐based genomic array profiling is a high‐resolution tool that also enables genome wide analysis. We compared karyotyping with oligo/SNP‐based array profiling in 104 MDS patients from the HOVON‐89 study. Oligo/SNP‐array identified all cytogenetically defined genomic lesions, except for subclones in two cases and balanced translocations in three cases. Conversely, oligo/SNP‐based genomic array profiling had a higher success rate, showing 55 abnormal cases, while an abnormal karyotype was found in only 35 patients. In nine patients whose karyotyping was unsuccessful because of insufficient metaphases or failure, oligo/SNP‐based array analysis was successful. Based on cytogenetic visible abnormalities as identified by oligo/SNP‐based genomic array prognostic scores based on IPSS/‐R were assigned. These prognostic scores were identical to the IPSS/‐R scores as obtained with karyotyping in 95%‐96% of the patients. In addition to the detection of cytogenetically defined lesions, oligo/SNP‐based genomic profiling identified focal copy number abnormalities or regions of copy neutral loss of heterozygosity that were out of the scope of karyotyping and fluorescence in situ hybridization. Of interest, in 26 patients we demonstrated such cytogenetic invisible abnormalities. These abnormalities often involved regions that are recurrently affected in hematological malignancies, and may therefore be of clinical relevance. Our findings indicate that oligo/SNP‐based genomic array can be used to identify the vast majority of recurrent cytogenetic abnormalities in MDS. Furthermore, oligo/SNP‐based array profiling yields additional genetic abnormalities that may be of clinical importance.